Career Exploration Predicts Career Decision-Making among Final-Year Students in Islamic Higher Education - Muhammad Nikman Naser; Robi Riyansyah; Fuad Maji; Najwa Rahmatunnisa; Dwiza Anggara; Rofiza Nabilla; Henda Resmiati; Novita Sari; Lioni Tri Munica; Muhammad Azizy (Pamomong: Journal of Islamic Educational Counseling, 2026)
Final-year students in Islamic higher education often face difficulties in making career decisions during the transition from university to employment. Although career exploration is widely recognized as an important component of career development, empirical evidence on its predictive contribution to career decision-making in Islamic higher education remains limited. This study examined whether career exploration predicts career decision-making and identified the level of career exploration among final-year students. A quantitative correlational survey design was used with 113 final-year students selected through purposive sampling. Data were collected using career exploration and career decision-making scales and analyzed using descriptive statistics and simple linear regression. Reliability analysis showed Cronbach’s alpha values of .837 for the career exploration scale and .926 for the career decision-making scale. The results indicated that career exploration was a positive and significant predictor of career decision-making (B = 1.076, β = .729, p < .001). The regression model explained 53.2% of the variance in career decision-making (R² = .532), suggesting that students with higher career exploration tended to report stronger career decision-making ability. Descriptive analysis showed that most respondents had a moderate level of career exploration (64.6%), followed by high (28.3%) and low (7.1%) levels. These findings may inform Islamic value-based career counseling services that help students explore career options and make more reflective decisions. This study is limited by its correlational design, self-report data, and single-institution sample. Future research should examine additional variables, use longitudinal or mixed-methods designs, and involve broader Islamic higher education contexts.